2020
DOI: 10.3390/sym12020214
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Bioconvective and Thermally Dissipation Flow of Viscoelastic Nanoparticles with Activation Energy Features: Novel Biofuels Significance

Abstract: The analysis of bioconvection flow nanofluids is the topic of concern in recent decades as it involves a variety of physical significance in biotechnology. Bioconvection has many applications in the interdisciplinary field of sciences such as in biomedical science, biofuel biotechnology, and enzyme-based biosensors, among others. The aim of the current work is to analyze the bioconvection phenomenon in the two-dimensional steady flow of viscoelastic nanofluid over a vertical surface. Here, the effects of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…They achieved that, hybrid nanoliquid displays a bigger heat transfer rate in contrast with the ordinary nanofluid. Waqas et al [7] revealed various uses related to the progression of nanoparticles within the sight of gyrotactic microbes. They utilized a secondgrade viscoelastic nanofluid pattern where the arithmetical arrangement has been determined by means of an implicit bvp4c calculation.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved that, hybrid nanoliquid displays a bigger heat transfer rate in contrast with the ordinary nanofluid. Waqas et al [7] revealed various uses related to the progression of nanoparticles within the sight of gyrotactic microbes. They utilized a secondgrade viscoelastic nanofluid pattern where the arithmetical arrangement has been determined by means of an implicit bvp4c calculation.…”
Section: Introductionmentioning
confidence: 99%
“…A flow model regarding bioconvection of Oldroyd-B nanoliquid in existence of activation energy generated by stretched cylinder was suggested by Tlili and co-workers [ 13 ]. Waqas et al [ 14 ] reported some biofuels application associated with the flow of nanoparticles in presence of gyrotactic microorganisms. They used a second grade viscoelastic nanofluid model where the numerical solution had been calculated via built-in bvp4c algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Waqas et al [29] examined the magnetohydrodynamics (MHD) flow of rate-type nanofluid in the presence of gyrotactic microorganisms with activation energy. Recently, Waqas et al [30] securitized the novel biofuel significance in viscoelastic nanofluid under the bioconvection process.…”
Section: Introductionmentioning
confidence: 99%